Volume 14: Processing and Engineering Applications of Novel Materials 2009
DOI: 10.1115/imece2009-12574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treating Temperature on Chemical and Physical Properties of Natural Hydroxyapatite Produced From Bovine Bone

Abstract: This study focused on chemical and physical properties of Hydroxyapatite powder was prepared by burning bone and heat treating the obtained bone ash at different temperatures (600, 700, 800, and 1100 °C) in an air furnace. The black ash was converted to a white powder after heat treatment. Results of X-ray diffraction analysis and Fourier transform infra-red spectroscopy that were done on heat treated powders in different temperatures indicated that the white powder was hydroxyapatite and did not contain any o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recently, sintering of animal bone at high temperatures has been suggested for the fabrication of protein-free natural bioceramics . Biological materials, such as corals, eggshells, cuttlefish bones, and bovine bones, etc., are also employed for the preparation of HA as bone substitutes for tissue engineering. Sintering of animal bone at higher temperatures facilitates the removal of all organic materials and forestalls the possibility of transmitting disease. Regarding the usage of PB, Haberko et al reported the natural behavior of HA during heat treatment by examining how the material reacts at high temperatures (<1000 °C) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, sintering of animal bone at high temperatures has been suggested for the fabrication of protein-free natural bioceramics . Biological materials, such as corals, eggshells, cuttlefish bones, and bovine bones, etc., are also employed for the preparation of HA as bone substitutes for tissue engineering. Sintering of animal bone at higher temperatures facilitates the removal of all organic materials and forestalls the possibility of transmitting disease. Regarding the usage of PB, Haberko et al reported the natural behavior of HA during heat treatment by examining how the material reacts at high temperatures (<1000 °C) .…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have attempted to synthesize HA from biological materials, including corals (Manjubala et al, 2000), eggshells (Rivera et al, 1999), cuttlefish bone (Venkatesan and Kim 2010;Kim et al, 2013), and bovine bones Ooi et al, 2007;Younesi et al, 2009;Hua et al, 2006). The sintered biological apatites have an interconnected porous structure, and therefore allow for faster bone ingrowth.…”
Section: Introductionmentioning
confidence: 99%